2005
DOI: 10.4319/lo.2005.50.6.1718
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony and seasonality in bacterioplankton communities of two temperate rivers

Abstract: The bacterioplankton community composition (measured with denaturing gradient gel electrophoresis of 16S ribosomal DNA [rDNA]) of two nonintersecting temperate rivers was nearly identical and changed synchronously over 2.5 yr, suggesting that intrinsic controls on bacteria were similar in the two rivers and that seasonal changes were driven by extrinsic factors such as climate. Most potential controls on community composition also exhibited synchrony; these included bacterial production rate (leucine incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
234
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(270 citation statements)
references
References 70 publications
26
234
5
Order By: Relevance
“…If temperature is indeed the main driver of community succession across seasonal and spatial thermal gradients, as has been proposed (Yannarell et al, 2003;Crump and Hobbie, 2005), then we must ask if bacterial communities adapted to high or low temperatures cycle elements differently from one another, and if so, how? If the manner in which we modeled our two species community is representative of natural communities, we would expect communities composed of cold-adapted species to have higher respiratory costs with increasing temperature relative to communities composed of warm-adapted populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If temperature is indeed the main driver of community succession across seasonal and spatial thermal gradients, as has been proposed (Yannarell et al, 2003;Crump and Hobbie, 2005), then we must ask if bacterial communities adapted to high or low temperatures cycle elements differently from one another, and if so, how? If the manner in which we modeled our two species community is representative of natural communities, we would expect communities composed of cold-adapted species to have higher respiratory costs with increasing temperature relative to communities composed of warm-adapted populations.…”
Section: Discussionmentioning
confidence: 99%
“…Such ambiguity most likely results from a variety of environmental and biological interactions with two key sources often being identified: (a) the interactive effects of temperature and resources on bacterial physiology and (b) changes in community composition of the bacterial community across temporal and spatial thermal gradients. While the interactive effects of nutrients on the metabolic response of bacteria to temperature have been thoroughly discussed in the literature (Pomeroy and Wiebe, 2001), only recently with the application of molecular techniques has it become clear that seasonal changes in community composition are common in marine and freshwater ecosystems (Pinhassi and Hagstrom, 2000;Crump and Hobbie, 2005;Fuhrman et al, 2006;Shade et al, 2007). Temperature is often suggested to be one of the primary drivers of seasonal succession in bacterial communities and also a key factor in recently described biogeographic patterns in marine bacterial communities (Pommier et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies that have examined the seasonal dynamics of prokaryotic communities have reported significant temporal trajectories across seasons, but incomplete or inconsistent interannual cycles (Lindstrom, 1998;Crump et al, 2003;Stepanauskas et al, 2003;Yannarell et al, 2003;Kent et al, 2004). Perhaps unsurprisingly, recent efforts to quantify synchronous temporal variation in spatially segregated microbial communities from similar environments have met with some success, likely due, in part, to the homogenization of regional climatic variability among study sites (Crump and Hobbie, 2005;Kent et al, 2007). A suite of more recent studies of lake, stream, estuarine, coastal and open ocean environments has shown recurring interannual patterns in bacterioplankton community structure by relying on high-frequency, multi-year data sets (Morris et al, 2005;Fuhrman et al, 2006;Hullar et al, 2006;Kan et al, 2006;Shade et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…DGGE gel images were analyzed by 'Quantity One' software in the GelDoc gel documentation system (Bio-Rad Laboratories, USA). Gel bands were identified using GelCompar software to create a presence-absence matrix (Crump and Hobbie 2005). Each band represents a bacterial operational taxonomic unit (OTU).…”
Section: Denaturating Gradient Gel Electrophoresis Analysismentioning
confidence: 99%